RETRACTED: Biosynthesis and characterization of iron oxide nanoparticles from Mentha spicata and screening its combating potential against Phytophthora infestans - Khan, Sidra; Bibi, Gulfam; Dilbar, Shazia; Iqbal, Aneela; Ahmad, Maaz; Ali, Ahmad; Ullah, Zahid; Jaremko, Mariusz; Iqbal, Javed; Ali, Mohammad; Haq, Ihtishamul; Ali, Iftikhar (Frontiers in Plant Science, 2022)
Plant pathogens causing serious diseases to agricultural cops which lead to food insecurity in the world. To combat plant pathogens, various strategies has been developed including the use of agrochemicals. The over use of these chemicals are now leading to pesticides resistant capability of pathogens. To overcome this problem, modern nanobiotechnology offers the production of alternative nano drugs. In this study, we used Mentha spicata for the synthesis of iron oxide nanoparticles using the green synthesis method. The synthesis of Fe2O3 NPs was confirmed through various characterizations. UV-Vis analysis detected a characteristic absorbance at the spectral range of 272nm. The SEM micrographic analysis at various magnifications displayed circular or rod shaped nanoparticles with a size ranging from 21 to 82 nm. The elemental EDX characterization showed intense peaks with a weight percent of 57, 34.93, 8.07 for Fe, O and chlorine respectively. TGA analysis showed that weight loss at 44-182, 500 and 660 oC with no further modification that indicates the thermal stability of iron oxide nanoparticles. FTIR spectrum of uncalined detects various bands at 3331, 1625 and 1437 cm-1 for hydroxyl group. After calcination two bands at 527 and 434 Cm-1 was observed for Fe-O. The antimicrobial in vitro study showed maximum growth inhibition of Phytophthora infestans by the concentration of 100 µg mL-1 of Fe2O3-PE and Fe2O3 NPs. Therefore, this study resulted that bio-stable iron oxide nanoparticles can be used as alternative antimicrobial agents.